Meniscus Tear Types and Early Failures in Pediaric Patients: Descriptive EPIDemiologic Analysis from the Score Multi-Center Quality Imrovment Project. Issue 5 (31st May 2022) - Peddireddy, Navya S.; Adsit, Lizzie R.; Cooper, Savannah; Milewski, Matthew; Heyworth, Benton; Edmonds, Eric; Pacicca, Donna; Bowen, Richard; Clark, Christian; Brey, Jennifer; Niu, Emily; Storer, Stephanie; et al.
Background: Meniscal tears have been reported at higher rates in the pediatric patient in recent years. Meniscus repair to restore meniscus function may be invaluable to the long-term health of the knee. Hypothesis/Purpose: To describe demographic characteristics, tear types, and surgical techniques for meniscus repair in pediatric patients, including risk factors for early repair failure. Methods: A multi-center quality improvement registry (16 institutions, 26 surgeons) monitoring the safety of meniscus repairs was reviewed. Audit processes using CPT codes were designed to ensure that all consecutive cases were prospectively entered on patients <19 years old into a HIPAA-compliant electronic platform. Each meniscus repair case with a complication form was secondarily reviewed to ensure consistency of identification and grading. Demographics, tear type, repair technique, and implant type, when applicable, were included, and a common cause analysis was performed to evaluate risk factors for early repair failures. Results: 1230 meniscus repair cases (mean age 15.2, 5-19; Female 43.8%) were identified, consisting of 49.0% lateral meniscus repair (LMR), 36.0% medial meniscus repair (MMR), and 15.0% LMR+MMR. The majority (69.7%) were performed in conjunction with either ACL reconstruction (ACLr) or tibial spine repair (TSr). In both LMR and MMR, the most common tear type, technique, and implant were longitudinal/vertical tear (50.3%, 80.0%, respectively), all-inside repair (69.3%, 68.9%, respectively), and Smith & Nephew Fast-Fix 360 (37.8%, 36.8%, respectively). An inside-out repair was performed twice as often in both LMR and MMR when performed in isolation without an ACLr or TSr. For both LMR and MMR, surgeons used an average of 2 sutures/devices (38.0%) with 6.5% involving 10+ sutures/implants. Variation in meniscus repair techniques was seen between tear types, displacement, and location (Tables 1, 2). Radial tears were uncommon in the MM (2.7%), but were commonly treated in the LM (12.32%) using all-inside (42.1%), inside-out (30.2%), and outside-in (19.7%) techniques. Meniscus tears with displacement were seen in 35.2% of MM tears and 25.3% of LM tears, with anterior displacement being the most common direction. For both LMR and MMR, the most common technique for tears with displacement was all-inside (58.4%). There were 15 early (<8 months) repair failures (1.2%), most common type and technique of which were MMR (73.3%) and all-inside (73.3%). Conclusion: The techniques utilized for pediatric meniscus tears depend upon tear type, displacement, and whether performed in conjunction with an ACLr or TSr. MMR performed with all-inside technique may be at risk for early failure. Table 1: Pediatric Lateral Meniscus tear and repair types from SCORE (a multi-center quality improvement registry) Table 2: Pediatric Medial Meniscus tear and repair types from SCORE (a multi-center quality improvement registry)